Gamificación como estrategia didáctica en las ciencias sociales (monografía de compilación) (2021)
This degree work is a compilation monograph based on the approach, knowledge and recognition of Gamification as a proposal for the implementation of methodologies, strategies and didactics to apply in the pedagogical work of teachers. There, it will be possible to show the strengths that this tool enhances in the classrooms, the projection of motivation and active learning that it fosters in students, the above, based on a systematic tour of theoretical references studied, examined and compared in depth